2017
DOI: 10.1371/journal.pone.0188633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy on activity and concentration of serum paraoxonase-1 in breast cancer patients

Abstract: Paraoxonase-1 (PON1) is an intra-cellular antioxidant enzyme found also in the circulation associated with high-density lipoproteins. The activity of this enzyme has been shown to be decreased in breast cancer (BC) patients. The aims of our study were to investigate the changes produced by radiotherapy (RT) on activity and concentration of serum PON1 in BC patients, and to evaluate the observed variations in relation to clinical and pathological characteristics of patients and tumors, and the response to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Although we did not evaluate the mechanism for the increase in PON1 activity in our study, it has been shown that simvastatin can modulate gene expression of this enzyme [50]. Recent studies report a decrease in serum PON1 activity in breast cancer patients [51,52], and it has been suggested that serum PON1 concentration could be an efficient prognostic biomarker for the success of radiotherapy in patients with breast cancer [53]; therefore, it seems that the ability of simvastatin in increasing PON1 activity may help in its therapeutic effect on chemicalinduced breast cancer, as observed in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Although we did not evaluate the mechanism for the increase in PON1 activity in our study, it has been shown that simvastatin can modulate gene expression of this enzyme [50]. Recent studies report a decrease in serum PON1 activity in breast cancer patients [51,52], and it has been suggested that serum PON1 concentration could be an efficient prognostic biomarker for the success of radiotherapy in patients with breast cancer [53]; therefore, it seems that the ability of simvastatin in increasing PON1 activity may help in its therapeutic effect on chemicalinduced breast cancer, as observed in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Measurement of PON1 post-radiotherapy could be an effective clinical biomarker of hepatic and systemic oxidative stress and may be used as an index of the usefulness of radiotherapy. 50 It has been demonstrated to catalyze hydrolysis of lipid hydroperoxides and lactones. 51 PON1 protects serum HDL and LDL particles against lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…They were patients at the Department of Radiation Oncology of Hospital Sant Joan (Reus, Spain). All patients had a Karnofsky Index <70 and were classified as 0 or 1 on the Eastern Cooperative Oncology Group scale [39]. The protocol for metastatic BC patients (2.94%) was to proceed to RT following complete response of the metastases to primary systemic treatment [39].…”
Section: Methodsmentioning
confidence: 99%